Financial Ratio Analysis as A Tool for Assessing Company Performance - Naomi Napitupulu; Yosi Sihombing; Ester Naibaho; Sara Manik; Hamonangan Siallagan (CV Putra Publisher, 2026)
Company performance assessment is a crucial aspect of economic decision-making for both internal and external stakeholders. One of the most widely used approaches to evaluating company performance is financial ratio analysis. This study aims to theoretically examine the role of financial ratio analysis as a tool for assessing company performance. The research employs a literature review method with a descriptive qualitative approach, using secondary data obtained from accounting textbooks, scientific journals, and relevant literature on financial statement analysis. The analysis focuses on four main categories of financial ratios, namely liquidity ratios, solvency ratios, profitability ratios, and activity ratios. The findings indicate that liquidity ratios provide insights into a company's ability to meet short-term obligations, solvency ratios reflect the company's capital structure and level of financial risk, profitability ratios measure the company's ability to generate earnings, and activity ratios indicate the efficiency of asset utilization. Theoretically, the integration of these four groups of financial ratios enables a comprehensive evaluation of company performance. Therefore, financial ratio analysis can be considered a relevant and systematic tool for assessing company performan